2019
DOI: 10.1097/won.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pressure Injuries on Patient Outcomes in a Korean Hospital

Abstract: PURPOSE: The purpose of this study was to compare the effect of pressure injuries on mortality, hospital length of stay, healthcare costs, and readmission rates in hospitalized patients. DESIGN: A case-control study. SUBJECTS AND SETTING: The sample comprised 5000 patients admitted to a tertiary hospital located in Seoul Korea; 1000 patients with pressure injuries (cases) were compared to 4000 patients who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…1,2 These ulcers can be associated with various issues for the patient and the healthcare system including an increase in the costs, whether during hospitalization or after hospital discharge, an increase in the length of stay in hospital, and an increase in the need for readmission. 3 In addition, the development of pressure injuries in a patient can lead to psychological problems, lower self-esteem, and lower quality of life. 4,5 Excessive pressure on the capillaries of the skin and their blockage are the main causes of pressure injuries development.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These ulcers can be associated with various issues for the patient and the healthcare system including an increase in the costs, whether during hospitalization or after hospital discharge, an increase in the length of stay in hospital, and an increase in the need for readmission. 3 In addition, the development of pressure injuries in a patient can lead to psychological problems, lower self-esteem, and lower quality of life. 4,5 Excessive pressure on the capillaries of the skin and their blockage are the main causes of pressure injuries development.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure injury can cause prolonged hospitalization. Han et al [22] reported that pressure injuries influenced mortality (OR 2.18) and increased the risk of increased hospital stay (OR 5.55), along with increased risk of readmission (OR 1.30) and emergency department visits after discharge (OR 1.70). Analysis of the association between pressure injury and medical costs requires further research using substantial data.…”
Section: 004mentioning
confidence: 99%
“…[ 5 6 ] The incidence of these wounds in the ICU of South Korean hospitals was 5.9%. [ 7 ] In Iran, the prevalence of PUs was reported to be 5% in general wards and 21%–1.10% in the ICUs. [ 2 ] One of the major health problems is PU leading to increased hospitalization time, pain, infection, chronic wounds, sepsis, and death.…”
Section: Introductionmentioning
confidence: 99%